If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9.6=y/3-2.1
We move all terms to the left:
-9.6-(y/3-2.1)=0
We get rid of parentheses
-y/3+2.1-9.6=0
We multiply all the terms by the denominator
-y+(2.1)*3-(9.6)*3=0
We add all the numbers together, and all the variables
-1y-22.5=0
We move all terms containing y to the left, all other terms to the right
-y=22.5
y=22.5/-1
y=-22+0.5/1
| a-34=47 | | 4x=7=-29 | | 5/7x+5=10 | | t÷5-2=10 | | 7^x=412 | | 6x-15+x+19.5=180 | | -20x+10=-6+-12x | | -6n=8 | | 51(x+4)=20(2x-1) | | 8x+3=8x+3=4.7x-(-2.8x-3.7)4.7x−(−2.8x−3.7) | | 8−3p=5 | | 2v+5v+2=12- | | x5=78 | | 23+y=56y= | | 83=-7+5n-5 | | -64x+42=-6x-22 | | 51(x+4)=57(2x-1) | | 2.5x=x+72 | | 12(x+1)=20(3x-2) | | -0.8(x-14)=24 | | 5x=x=72 | | 8m=3=59 | | 6x+10/2=32 | | 2x+14=27 | | -0.8(x-14)=-30 | | 3=3u-6 | | 7/n=3/8 | | 4r=18-2r | | 8=4+v/4 | | z5+4=−75 | | z/5+4=−75 | | y+72=9y |